The Model of Kitab Mutammimah Al-Ajurumiyyah Card Series Development Based on Mind Mapping for Student - Ahmad Kausari; Ridha Darmawaty; Fatwiyah Noor (Universitas Islam Negeri Palangka Raya, 2023)
The use of Arabic learning media in Salafiyah Islamic boarding schools in Balangan Regency is considered infrequent, causing the necessity to develop learning media to be accepted and used. This research aims to create a model of a mind mapping-based card series of Kitab Mutammimah al-Ajurumiyyah for students' grammar learning at Salafiyah Islamic boarding schools. This development research using the ADDIE model comprises potential analysis, product design, product development, field implementation, and evaluation. According to the results of teachers